The Evolution of Arabic Language Teaching Methods in Indonesia: A Bibliometric Analysis of Research Publications over the Last Fifteen Years - Faruq Abdul Muid; Taufik Siraj; Hasyim Asyari; Wahidiyat Nur Laduni (Learning, Media and Technology in Arabic Education, 2026)
Arabic language education in Indonesia has continued to evolve in response to changing pedagogical demands and the rapid expansion of digital technology. This study aimed to map the development of Arabic language teaching methods in Indonesia from 2010 to 2024 and to identify shifts in research attention across six categories: Traditional Methods associated with pesantren education, Grammar–Translation Methods, Audio-Lingual Methods, Communicative Methods, Integrated Approaches, and Technology-Based Learning. A descriptive bibliometric mapping design was employed using publications retrieved from Google Scholar through Publish or Perish. From an initial pool of 500 records, 71 publications met the inclusion criteria and were classified according to publication year and dominant instructional orientation. The results showed that Traditional Methods had the broadest temporal presence, while Grammar–Translation, Audio-Lingual, Communicative, and Integrated Approaches appeared more intermittently. The most notable pattern was the rapid growth of Technology-Based Learning after 2020, culminating in 18 publications in 2024, which represented the highest annual count in the dataset. These findings indicate that Arabic language teaching in Indonesia is not shifting through the complete replacement of traditional approaches, but through their gradual coexistence with communicative, integrated, and digitally mediated practices. The study concludes that future development should emphasize context-sensitive integration between established pedagogical foundations and emerging technologies to support more flexible, interactive, and sustainable Arabic language learning.